Evaluating the relevance of tasks in EFL textbooks "Think Globally Act Locally" / Aryani Aryani, Rofiza Aboo Bakar and Regina Regina - Aryani, Aryani; Aboo Bakar, Rofiza; Regina, Regina (Universiti Teknologi MARA, Pulau Pinang, 2022)
The Indonesian government has published students' textbooks and teacher guidance books as compulsory textbooks for the teaching and learning process following the 2013 curriculum. To ensure that textbooks are of quality, teachers should know the strengths and weaknesses of tasks in the published textbooks. Thus, evaluation of tasks in the aforesaid textbooks is crucial. This article evaluated the relevance of tasks in English Foreign Learners (EFL) Textbooks "Think Globally Act Locally" (TGAL) in the 2013 Curriculum. It investigated the completeness of components and categories of tasks. Qualitative content analysis was utilized, and analysis sheets (TAS) were used as the analysis tools. The researchers chose 4 chapters which represented all the important tasks in the textbooks. The standard 2013 Curriculum was used as the guideline for evaluation. The procedures undertaken were finding out the tasks, coding, matching the criteria, totaling, and finding the percentage. The result showed that input, output, activities, setting, and teacher's and student's roles in TGAL EFL textbooks fulfilled the criteria of tasks in the 2013 Curriculum. The researchers suggest that this finding be used by policy makers to further enhance the TGAL EFL textbooks.